Mast cell activation mediates blood–brain barrier impairment and cognitive dysfunction in septic mice in a histamine-dependent pathway - Yue, Jianhe; Tan, Ying; Huan, Renzheng; Guo, Jin; Yang, Sha; Deng, Mei; Xiong, Yunbiao; Han, Guoqiang; Liu, Lin; Liu, Jian; Cheng, Yuan; Zha, Yan; et al. (Frontiers in Immunology, 2023)
Introduction Sepsis-associated encephalopathy (SAE) is a diffuse cerebral dysfunction resulting from a systemic inflammatory response to infection; however, its pathophysiology remains unclear. Sepsis-induced neuroinflammation and blood–brain barrier (BBB) disruption are crucial factors in brain function disturbance in SAE. Mast cells (MCs) activation plays an important role in several neuroinflammation models; however, its role in SAE has not been comprehensively investigated. Methods We first established a SAE model by cecal ligation puncture (CLP) surgery and checked the activation of MCs. MCs activation was checked using immumohistochemical staining and Toluidine Blue staining. We administrated cromolyn (10mg/ml), a MC stabilizer, to rescue the septic mice. Brain cytokines levels were measured using biochemical assays. BBB disruption was assessed by measuring levels of key tight-junction (TJ) proteins. Cognitive function of mice was analyzed by Y maze and open field test. Transwell cultures of brain microvascular endothelial cells (BMVECs) co-cultured with MCs were used to assess the interaction of BMVECs and MCs. Results Results showed that MCs were overactivated in the hippocampus of CLP-induced SAE mice. Cromolyn intracerebroventricular (i.c.v) injection substantially inhibited the MCs activation and neuroinflammation responses, ameliorated BBB impairment, improved the survival rate and alleviated cognitive dysfunction in septic mice. In vitro experiments, we revealed that MCs activation increased the sensitivity of BMVECs against to lipopolysaccharide (LPS) challenge. Furthermore, we found that the histamine/histamine 1 receptor (H1R) mediated the interaction between MCs and BMVECs, and amplifies the LPS-induced inflammatory responses in BMVECs by modulating the TLR2/4-MAPK signaling pathway. Conclusions MCs activation could mediate BBB impairment and cognitive dysfunction in septic mice in a histamine-dependent pathway.